Aluminum nitride thermal interface material with high compressive strength and preparation method thereof

The thermal interface material with modified glass fiber and aluminum nitride silicone addresses compressive strength issues by enhancing bonding and structural support, achieving high strength and conductivity.

CN119192849APending Publication Date: 2024-12-27ZHENGZHOU NON FERROUS METALS RES INST CO LTD OF CHALCO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411297241.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing thermal interface materials using aluminum nitride suffer from poor compressive strength when thickness is below 0.5 mm, leading to deformation and tearing.

Method used

A thermal interface material comprising modified glass fiber and aluminum nitride thermally conductive silicone, with specific ratios of continuous mesh glass fiber, nano alumina powder, and coupling agent, along with aluminum nitride thermal conductive powder, vinyl silicone oil, and surface treatment agents, to enhance bonding and compressive strength.

Benefits of technology

The material achieves high compressive strength and improved thermal conductivity, overcoming the limitations of previous materials by ensuring structural integrity and effective heat transfer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192849A_ABST
    Figure CN119192849A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of thermal interface materials, in particular to an aluminum nitride thermal interface material with high compressive strength and a preparation method thereof. The aluminum nitride thermal interface material comprises: modified glass fiber; and at least one layer of aluminum nitride heat-conducting silica gel. The at least one layer of aluminum nitride heat-conducting silica gel is arranged on one side surface or two side surfaces of the modified glass fiber; the modified glass fiber comprises the following raw materials: continuous reticular glass fiber, nano aluminum oxide powder and a coupling agent, and the weight m1 of the continuous reticular glass fiber, the weight m2 of the nano aluminum oxide powder and the weight m3 of the coupling agent meet the relational expression: m1: m2: m3 = (950-1000): (5-50): (0-30). The surface of the continuous reticular glass fiber is modified by the nano aluminum oxide powder and the coupling agent, then the continuous reticular glass fiber is used as a support body, and the compressive strength of the aluminum nitride thermal interface material is improved to 100 MPa or above based on the strength and toughness characteristics of the continuous reticular glass fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of thermal interface materials, and in particular to an aluminum nitride thermal interface material with high compressive strength and a preparation method thereof. Background Art

[0002] Ordinary thermal interface materials are made of alumina and silica gel. The thermal conductivity of these thermal interface materials generally does not exceed 8W / mK. Aluminum nitride has high thermal conductivity and high insulation, and the theoretical value of aluminum nitride single crystal is 320W / (m·K), and the actual value can still reach 100W / (m·K)~280W / (m·K), which is equivalent to 5 to 10 times the actual value of aluminum oxide single crystal. In order to increase the thermal conductivity of thermal interface materials, existing research has also attempted to use aluminum nitride as a filler to improve the thermal conductivity of thermal interface materials, but aluminum nitride is easily hydrolyzed and generates aluminum hydroxide, and the generated aluminum hydroxide will interrupt the heat conduction path, thereby affecting the heat transfer in the entire network chain; therefore, at this stage, aluminum nitride is treated with anti-hydrolysis to improve its anti-hydrolysis properties.

[0003] However, at present, the thickness of the thermal interface material using aluminum nitride needs to be kept above 0.5 mm for strength considerations. However, when the thickness of the thermal interface material is below 0.5 mm, the strength of the thermal interface material is poor, which may cause deformation and tearing of the thermal interface material. Summary of the invention

[0004] The present application provides an aluminum nitride thermal interface material with high compressive strength and a preparation method thereof, in order to solve the following technical problem: how to improve the compressive strength of the aluminum nitride thermal interface material.

[0005] In a first aspect, the present application provides an aluminum nitride thermal interface material with high compressive strength, the aluminum nitride thermal interface material comprising: modified glass fiber; and

[0006] At least one layer of aluminum nitride thermally conductive silicone; at least one layer of the aluminum nitride thermally conductive silicone is disposed on one side surface or both sides surface of the modified glass fiber;

[0007] The raw materials of the modified glass fiber include: continuous mesh glass fiber, nano alumina powder and a coupling agent. The weight m1 of the continuous mesh glass fiber, the weight m2 of the nano alumina powder and the weight m3 of the coupling agent satisfy the relationship: m1:m2:m3=(950-1000):(5-50):(0-30).

[0008] Optionally, the continuous mesh glass fiber includes a plurality of glass fibers, the average diameter of the plurality of glass fibers is 2 μm to 30 μm, and the average distance between two adjacent glass fibers is 20 μm to 300 μm.

[0009] Optionally, the particle size of the nano alumina powder is 15nm to 100nm;

[0010] The coupling agent includes at least one of the following:

[0011] KH-550 coupling agent, KH-560 coupling agent and KH-570 coupling agent.

[0012] Optionally, the raw materials of the aluminum nitride thermal conductive silica gel include, by weight:

[0013] Aluminum nitride thermal conductive powder: 2600 parts to 2880 parts, vinyl silicone oil: 100 parts to 300 parts, gelling agent: 5 parts to 15 parts, adhesive: 1 part to 3 parts, inhibitor: 0.01 parts to 1 part and surface treatment agent: 10 parts to 90 parts.

[0014] Optionally, the aluminum nitride thermally conductive powder comprises, by weight, 480 to 520 parts of first-grade aluminum nitride powder, 800 to 870 parts of second-grade aluminum nitride powder, and 1400 to 1500 parts of third-grade aluminum nitride powder;

[0015] The particle size of the first-grade aluminum nitride powder is 0.6 μm to 1.0 μm, the particle size of the second-grade aluminum nitride powder is 8 μm to 12 μm, and the particle size of the third-grade aluminum nitride powder is 118 μm to 122 μm.

[0016] Optionally, the surface treatment agent includes, by weight: polyvinyl alcohol: 30 to 100 parts, KH-570 coupling agent: 1 to 10 parts, polybutadiene: 5 to 20 parts.

[0017] Optionally, the viscosity of the vinyl silicone oil is 20 cPs to 200 cPs;

[0018] The gelling agent includes hydrogen-containing silicone oil;

[0019] The adhesive includes a platinum catalyst.

[0020] In a second aspect, the present application provides a method for preparing the aluminum nitride thermal interface material according to the first aspect, the method comprising:

[0021] The nano-alumina powder and the organic solvent are stirred and mixed to obtain a nano-alumina suspension;

[0022] Using the nano-alumina suspension to first impregnate the continuous mesh glass fiber, and then drying the first impregnated continuous mesh glass fiber to obtain pretreated continuous mesh glass fiber;

[0023] Using a coupling agent solution to perform a second impregnation on the pretreated continuous mesh glass fiber, and then drying the pretreated continuous mesh glass fiber after the second impregnation to obtain a modified glass fiber;

[0024] The aluminum nitride thermal conductive silica gel and the modified glass fiber are compression molded, and then the molded product is vulcanized and cooled to obtain the aluminum nitride thermal interface material.

[0025] Optionally, the first infiltration time is ≥15 min, and the second infiltration time is ≥20 min;

[0026] The vulcanization temperature is 100° C. to 130° C., and the vulcanization time is 15 min to 35 min.

[0027] Optionally, the method further includes:

[0028] The surface treatment agent and the aluminum nitride thermal conductive powder are stirred and mixed, and then the stirred and mixed mixture is dried to modify the aluminum nitride thermal conductive powder by the surface treatment agent to obtain a surface-modified thermal conductive powder;

[0029] Mixing vinyl silicone oil, a gelling agent, an adhesive and an inhibitor to obtain a mixing auxiliary agent;

[0030] The mixing aid and the surface-modified thermally conductive powder are mixed to obtain aluminum nitride thermally conductive silica gel.

[0031] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0032] The embodiment of the present application provides an aluminum nitride thermal interface material with high compressive strength. The modified glass fiber is arranged on the surface of the aluminum nitride thermal conductive silicone. In addition, the raw materials of the modified glass fiber include: continuous mesh glass fiber, nano-alumina powder and coupling agent, and the weight m1 of the continuous mesh glass fiber, the weight m2 of the nano-alumina powder and the weight m3 of the coupling agent satisfy the relationship: m1:m2:m3=(950-1000):(5-50):(0-30). The surface of the continuous mesh glass fiber is modified by the nano-alumina powder to improve The degree of bonding between the continuous mesh glass fiber and the aluminum nitride thermal conductive silicone can be improved by modifying the continuous mesh glass fiber with a coupling agent, so as to improve the bonding strength between the continuous mesh glass fiber and the aluminum nitride thermal conductive silicone. The continuous mesh glass fiber and the aluminum nitride thermal conductive silicone with high bonding strength or degree can use the continuous mesh glass fiber as a support, thereby improving the compressive strength of the aluminum nitride thermal conductive silicone based on the strength and toughness characteristics of the continuous mesh glass fiber. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0034] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0035] Figure 1 A schematic diagram of the structure of an aluminum nitride thermal interface material with high compressive strength provided in an embodiment of the present application;

[0036] Figure 2 A schematic flow chart of a method for preparing an aluminum nitride thermal interface material provided in an embodiment of the present application;

[0037] Figure 3 A detailed schematic diagram of a method for preparing an aluminum nitride thermal interface material provided in an embodiment of the present application. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0039] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within the range; for example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which applies regardless of the range; in addition, whenever a numerical range is indicated in this document, it is meant to include any cited numbers (fractions or integers) within the indicated range.

[0040] In this document, the terms "including" and "comprising" mean "including but not limited to". Relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0041] Figure 1 The schematic diagram of the structure of an aluminum nitride thermal interface material with high compressive strength provided in an embodiment of the present application is exemplarily shown;

[0042] like Figure 1 As shown, the embodiment of the present application provides an aluminum nitride thermal interface material with high compressive strength, the aluminum nitride thermal interface material comprising: modified glass fiber; and at least one layer of aluminum nitride thermal conductive silicone; at least one layer of the aluminum nitride thermal conductive silicone is disposed on one side surface or both sides of the modified glass fiber;

[0043] The raw materials of the modified glass fiber include: continuous mesh glass fiber, nano alumina powder and a coupling agent. The weight m1 of the continuous mesh glass fiber, the weight m2 of the nano alumina powder and the weight m3 of the coupling agent satisfy the relationship: m1:m2:m3=(950-1000):(5-50):(0-30).

[0044] The weight m1 of the continuous mesh glass fiber, the weight m2 of the nano alumina powder and the weight m3 of the coupling agent satisfy the relationship: m1:m2:m3=950:50:0, 950:40:10, 950:30:20, 950:20:30, 960:40:0, 960:30:10, 960:20:20, 960:10:30, 970:30:0, 970:20:10, 970:10:20, 970:5:25, 980:20:0, 980:10:10, 980:5:15, 990:10:0, 990:5:5.

[0045] It should be noted that the number of layers of aluminum nitride thermal conductive silicone can be 1 layer, 2 layers, 3 layers, 4 layers, etc. For example, multiple layers of the aluminum nitride thermal conductive silicone can be stacked on one side surface of the modified glass fiber; or can be respectively arranged on both sides of the modified glass fiber. Preferably, the number of layers of aluminum nitride thermal conductive silicone is 2 layers, and the modified glass fiber is arranged between the 2 layers of aluminum nitride thermal conductive silicone.

[0046] It should be noted that the modified glass fiber is obtained by performing various modifications on the continuous mesh glass fiber based on the properties of aluminum nitride thermal conductive silica gel.

[0047] It should be noted that the aluminum nitride thermal conductive silicone is a soft matrix, and general continuous mesh glass fibers are difficult to combine with such a soft matrix, which increases the difficulty of the continuous mesh glass fibers in increasing the strength of the aluminum nitride thermal conductive silicone.

[0048] In some optional embodiments, the continuous mesh glass fiber includes a plurality of glass fibers, the average diameter of the plurality of glass fibers is 2 μm to 30 μm, and the average spacing between two adjacent glass fibers is 20 μm to 300 μm;

[0049] In these embodiments, the continuous mesh glass fiber may include multiple glass fibers, and the average spacing between two adjacent glass fibers may be 20 μm to 300 μm. The use of continuous mesh glass fibers with larger pore sizes can uniformly improve the compressive strength of the aluminum nitride thermal conductive silicone. In addition, the average diameter of the multiple glass fibers can be 2 μm to 30 μm, which can reduce the thickness of the continuous mesh glass fibers.

[0050] The average distance between two adjacent glass fibers may be 20 μm, 30 μm, 40 μm, 50 μm, 100 μm, 150 μm, 200 μm, 250 μm or 300 μm.

[0051] The plurality of glass fibers may have an average diameter of 2 μm, 3 μm, 4 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, or 30 μm.

[0052] In some optional embodiments, the particle size of the nano alumina powder is 15 nm to 100 nm;

[0053] The coupling agent includes at least one of the following:

[0054] KH-550 coupling agent, KH-560 coupling agent and KH-570 coupling agent;

[0055] In these embodiments, the particle size of the nano-alumina powder can be 15nm to 100nm, indicating that the particles of the nano-alumina powder are finer, and the nano-alumina powder with finer particles can improve the surface modification effect of the nano-alumina powder on the continuous mesh glass fiber, thereby effectively improving the bonding degree between the continuous mesh glass fiber and the aluminum nitride thermal conductive silicone. The continuous mesh glass fiber and the aluminum nitride thermal conductive silicone with a high bonding degree can use the continuous mesh glass fiber as a support, thereby improving the thermal conductivity of the aluminum nitride based on the strength and toughness characteristics of the continuous mesh glass fiber. The compressive strength of the silicone rubber; in addition, the coupling agent may include: at least one of KH-550 coupling agent, KH-560 coupling agent and KH-570 coupling agent. The continuous mesh glass fiber is modified based on the modification effect of the coupling agent, and the bonding strength between the continuous mesh glass fiber and the aluminum nitride thermal conductive silicone rubber can be improved. The continuous mesh glass fiber with high bonding strength and the aluminum nitride thermal conductive silicone rubber can use the continuous mesh glass fiber as a support, thereby improving the compressive strength of the aluminum nitride thermal conductive silicone rubber based on the strength and toughness characteristics of the continuous mesh glass fiber.

[0056] The particle size of the nano alumina powder can be 15nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm or 100nm.

[0057] In some optional embodiments, the raw materials of the aluminum nitride thermal conductive silica gel include, by weight:

[0058] Aluminum nitride thermal conductive powder: 2600 parts to 2880 parts, vinyl silicone oil: 100 parts to 300 parts, gelling agent: 5 parts to 15 parts, adhesive: 1 part to 3 parts, inhibitor: 0.01 parts to 1 part and surface treatment agent: 10 parts to 90 parts;

[0059] In these embodiments, the raw materials of aluminum nitride thermal conductive silicone may include: aluminum nitride thermal conductive powder: 2600 parts to 2880 parts, and the aluminum nitride thermal conductive powder may be used to improve the thermal conductivity and thermal insulation effects of the aluminum nitride thermal conductive silicone; in addition, the raw materials of the aluminum nitride thermal conductive silicone may include a gelling agent: 5 parts to 15 parts and an adhesive: 1 part to 3 parts, and the tightness between the aluminum nitride thermal conductive powder in the aluminum nitride thermal conductive silicone is improved through the cross-linking effect of the gelling agent and the vulcanization effect of the adhesive, so as to improve the compression rate of the aluminum nitride thermal conductive silicone; in addition, the raw materials of the aluminum nitride thermal conductive silicone may include: an inhibitor: 0.01 parts to 1 parts, and the inhibitory effect of the inhibitor reduces the quality of the gelling agent, the adhesive and the vinyl silicone oil. The risk of change can be reduced, so that aluminum nitride thermal conductive silicone with good compression rate and hardness can be obtained. In addition, the raw materials of aluminum nitride thermal conductive silicone can include: surface treatment agent: 10 parts to 90 parts, and the aluminum nitride thermal conductive powder is modified to resist hydrolysis through the surface modification effect of the surface treatment agent to avoid the aluminum nitride thermal conductive powder being hydrolyzed to generate aluminum hydroxide impurities, which affects the thermal conductivity of the aluminum nitride thermal conductive powder; in addition, the raw materials of aluminum nitride thermal conductive silicone can include: vinyl silicone oil: 100 parts to 300 parts, using vinyl silicone oil as a carrier, and fully dispersing aluminum nitride thermal conductive powder, gelling agent, adhesive, inhibitor and surface treatment agent through vinyl silicone oil, so as to obtain aluminum nitride thermal conductive silicone with good compression rate and hardness.

[0060] The weight proportions of the aluminum nitride thermally conductive powder may be 2600, 2620, 2640, 2660, 2680, 2700, 2720, 2740, 2760, 2780, 2800, 2820, 2840, 2860 or 2880 parts.

[0061] The weight parts of the vinyl silicone oil can be 100 parts, 150 parts, 200 parts, 250 parts or 300 parts.

[0062] The weight proportions of the gelling agent can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts or 15 parts.

[0063] The weight proportion of the adhesive can be 1 part, 2 parts or 3 parts.

[0064] The weight portion of the inhibitor can be 0.01 part, 0.05 part, 0.10 part, 0.20 part, 0.30 part, 0.40 part, 0.50 part, 0.60 part, 0.70 part, 0.80 part, 0.90 part or 1.00 part.

[0065] The weight proportion of the surface treatment agent may be 10 parts, 20 parts, 30 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts or 90 parts.

[0066] In some optional embodiments, the aluminum nitride thermally conductive powder includes, by weight, 50 to 200 parts of first-grade aluminum nitride powder, 100 to 300 parts of second-grade aluminum nitride powder, and 400 to 700 parts of third-grade aluminum nitride powder;

[0067] Wherein, the particle size of the first particle size aluminum nitride powder is 0.6 μm to 1.0 μm, the particle size of the second particle size aluminum nitride powder is 8 μm to 12 μm, and the particle size of the third particle size aluminum nitride powder is 118 μm to 122 μm;

[0068] In these embodiments, the aluminum nitride thermal conductive powder may include 50 to 200 parts of a first grade aluminum nitride powder, 100 to 300 parts of a second grade aluminum nitride powder, and 400 to 700 parts of a third grade aluminum nitride powder, and the particle size of the first grade aluminum nitride powder may be 0.6 μm to 1.0 μm, the particle size of the second grade aluminum nitride powder may be 8 μm to 12 μm, and the particle size of the third grade aluminum nitride powder may be 118 μm to 122 μm. By stacking aluminum nitride powders of different particle sizes to form an aluminum nitride thermal conductive powder, the thermal conductivity and hardness characteristics of the aluminum nitride thermal conductive powder can be improved, and the density of the aluminum nitride thermal conductive powder can also be reduced, thereby improving the thermal conductivity, hardness characteristics, and volume resistivity of the aluminum nitride thermal conductive silicone rubber, thereby improving the compressive strength of the aluminum nitride thermal interface material.

[0069] The weight proportion of the first grade aluminum nitride powder can be 50 parts, 100 parts, 150 parts or 200 parts.

[0070] The weight proportion of the second grade aluminum nitride powder can be 100 parts, 150 parts, 200 parts, 250 parts or 300 parts.

[0071] The weight proportion of the third grade aluminum nitride powder can be 400 parts, 450 parts, 500 parts, 550 parts, 600 parts, 650 parts or 700 parts.

[0072] The particle size of the first particle size aluminum nitride powder can be 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm or 1.0 μm.

[0073] The particle size of the second particle size aluminum nitride powder can be 8 μm, 9 μm, 10 μm, 11 μm or 12 μm.

[0074] The particle size of the third particle size aluminum nitride powder can be 118 μm, 119 μm, 120 μm, 121 μm or 122 μm.

[0075] In some optional embodiments, the surface treatment agent includes, by weight: polyvinyl alcohol: 30 to 100 parts, KH-570 coupling agent: 1 to 10 parts, polybutadiene: 5 to 20 parts;

[0076] In these embodiments, the surface treatment agent may include: polyvinyl alcohol: 30 parts to 100 parts, KH-570 coupling agent: 1 part to 10 parts, polybutadiene: 5 parts to 20 parts, indicating that the surface treatment agent is a coupling modifier of a composite macromolecule, and the aluminum nitride thermal conductive powder is subjected to anti-hydrolysis modification through the surface modification effect of the coupling modifier of the composite macromolecule to prevent the aluminum nitride thermal conductive powder from being hydrolyzed to generate aluminum hydroxide impurities, which affects the thermal conductivity of the aluminum nitride thermal conductive powder.

[0077] The weight proportions of the polyvinyl alcohol can be 30 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts, 90 parts or 100 parts.

[0078] The weight proportions of the KH-570 coupling agent can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts.

[0079] The weight parts of the polybutadiene can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts.

[0080] In some optional embodiments, the viscosity of the vinyl silicone oil is 20 cPs to 200 cPs;

[0081] The gelling agent includes hydrogen-containing silicone oil;

[0082] The adhesive includes a platinum catalyst;

[0083] In these embodiments, the viscosity of the vinyl silicone oil can be 20cPs to 200cPs. The vinyl silicone oil is used as a carrier to fully disperse the aluminum nitride thermal conductive powder, gelling agent, adhesive, inhibitor and surface treatment agent through the vinyl silicone oil, so that aluminum nitride thermal conductive silicone with good compressibility and hardness can be obtained; in addition, the gelling agent can include hydrogen-containing silicone oil and the adhesive can include a platinum catalyst, and the tightness between the aluminum nitride thermal conductive powder in the aluminum nitride thermal conductive silicone is improved through the cross-linking effect of the gelling agent and the vulcanization effect of the adhesive, so as to improve the compression rate of the aluminum nitride thermal conductive silicone.

[0084] The viscosity of the vinyl silicone oil may be 20 cPs, 40 cPs, 60 cPs, 80 cPs, 100 cPs, 120 cPs, 140 cPs, 160 cPs, 180 cPs or 200 cPs.

[0085] Figure 2 A schematic flow chart of a method for preparing an aluminum nitride thermal interface material provided in an embodiment of the present application is exemplarily shown;

[0086] Based on a general inventive concept, such as Figure 2 As shown, the embodiment of the present application provides a method for preparing the aluminum nitride thermal interface material, the method comprising:

[0087] S1. The nano-alumina powder and the organic solvent are stirred and mixed to obtain a nano-alumina suspension;

[0088] S2. The continuous mesh glass fiber is first impregnated with the nano-alumina suspension, and then the continuous mesh glass fiber after the first impregnation is dried to obtain a pretreated continuous mesh glass fiber;

[0089] S3. The pretreated continuous mesh glass fiber is secondly impregnated with a coupling agent solution, and then the pretreated continuous mesh glass fiber after the second impregnation is dried to obtain a modified glass fiber;

[0090] S4. The aluminum nitride thermal conductive silica gel and the modified glass fiber are compression molded, and then the molded product is vulcanized and cooled to obtain an aluminum nitride thermal interface material.

[0091] This method is a method for preparing the above-mentioned aluminum nitride thermal interface material. The specific composition of the aluminum nitride thermal interface material can refer to the above-mentioned embodiment. Since this method adopts part or all of the technical solutions of the above-mentioned embodiment, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be repeated here one by one.

[0092] It should be noted that the drying can be performed in an oven, the drying temperature can be 80° C., and the drying time can be 2 h to 6 h.

[0093] It should be noted that the stirring and mixing speed may be 1600 r / min, and the stirring and mixing time may be 1 h.

[0094] In some optional embodiments, the first infiltration time is ≥15 min, and the second infiltration time is ≥20 min;

[0095] The vulcanization temperature is 100°C to 130°C, and the vulcanization time is 15min to 35min;

[0096] In these embodiments, the time of the first impregnation can be ≥15 minutes, and the time of the second impregnation can be ≥20 minutes. Through the two impregnation methods, the surface of the continuous mesh glass fiber is modified by the nano-alumina suspension and the coupling agent solution respectively, so as to effectively improve the bonding degree between the continuous mesh glass fiber and the aluminum nitride thermal conductive silicone rubber, thereby improving the compressive strength of the aluminum nitride thermal conductive silicone rubber based on the strength and toughness characteristics of the continuous mesh glass fiber; in addition, the vulcanization temperature can be 100°C to 130°C, and the vulcanization time is 15 minutes to 35 minutes. The bonding strength between the aluminum nitride thermal conductive silicone rubber and the modified glass fiber is improved by vulcanization, thereby improving the compressive strength of the aluminum nitride thermal conductive silicone rubber based on the strength and toughness characteristics of the continuous mesh glass fiber.

[0097] The vulcanization temperature may be 100°C, 105°C, 110°C, 115°C, 120°C, 125°C or 130°C.

[0098] The vulcanization time can be 15 min, 20 min, 25 min, 30 min, or 35 min.

[0099] Figure 3 A detailed schematic diagram of a method for preparing an aluminum nitride thermal interface material provided in an embodiment of the present application is exemplarily shown;

[0100] In some optional embodiments, such as Figure 3 As shown, the method also includes:

[0101] S401. The surface treatment agent and the aluminum nitride thermally conductive powder are stirred and mixed, and then the stirred and mixed mixture is dried to modify the aluminum nitride thermally conductive powder by the surface treatment agent to obtain a surface-modified thermally conductive powder;

[0102] S402. The vinyl silicone oil, gelling agent, adhesive and inhibitor are mixed to obtain a mixing aid;

[0103] S403. The mixing aid and the surface-modified thermally conductive powder are mixed to obtain aluminum nitride thermally conductive silica gel;

[0104] In these embodiments, the surface treatment agent and aluminum nitride thermal conductive powder are first stirred, mixed and dried to modify the aluminum nitride thermal conductive powder by the surface treatment agent, thereby improving the hydrolysis resistance of the aluminum nitride thermal conductive powder; in addition, vinyl silicone oil, gelling agent, adhesive and inhibitor are mixed to obtain a mixed auxiliary agent, which is convenient for subsequently obtaining aluminum nitride thermal conductive silicone with good compressibility and hardness.

[0105] The present application is further described below in conjunction with specific examples. The experimental methods in the following examples that do not specify specific conditions are usually measured according to industry standards; if there are no corresponding industry standards, they are carried out according to common international standards, conventional conditions, or conditions recommended by the manufacturer.

[0106] Example 1

[0107] like Figure 1 As shown, an aluminum nitride thermal interface material with high compressive strength, the aluminum nitride thermal interface material comprises: modified glass fiber and two layers of aluminum nitride thermal conductive silicone; the modified glass fiber is arranged between the two layers of aluminum nitride thermal conductive silicone;

[0108] Based on 1000 parts by weight, the raw materials of the modified glass fiber include: continuous mesh glass fiber, nano alumina powder and coupling agent, and the weight m1 of the continuous mesh glass fiber, the weight m2 of the nano alumina powder and the weight m3 of the coupling agent satisfy the relationship: m1:m2:m3=990:5:5.

[0109] The continuous mesh glass fiber includes a plurality of glass fibers, the average diameter of the plurality of glass fibers is 20 μm, and the average distance between two adjacent glass fibers is 200 μm.

[0110] The particle size of nano-alumina powder is 30nm;

[0111] The coupling agent is KH-560.

[0112] In parts by weight, the raw materials of aluminum nitride thermal conductive silicone include:

[0113] Aluminum nitride thermal conductive powder: 2690 parts, vinyl silicone oil: 279 parts, gelling agent: 15 parts, adhesive: 3 parts, inhibitor: 1 part and surface treatment agent: 12 parts.

[0114] In parts by weight, the aluminum nitride thermal conductive powder includes 480 parts of first-grade aluminum nitride powder, 810 parts of second-grade aluminum nitride powder and 1400 parts of third-grade aluminum nitride powder;

[0115] The particle size of the first-grade aluminum nitride powder is 0.8 μm, the particle size of the second-grade aluminum nitride powder is 10 μm, and the particle size of the third-grade aluminum nitride powder is 120 μm.

[0116] In parts by weight, the surface treatment agent includes: polyvinyl alcohol: 80 parts, KH-570 coupling agent: 10 parts, polybutadiene: 10 parts.

[0117] The viscosity of vinyl silicone oil is 100 cPs;

[0118] The gelling agent is hydrogen-containing silicone oil;

[0119] The adhesive is platinum catalyst.

[0120] like Figure 3 As shown, a method for preparing an aluminum nitride thermal interface material comprises:

[0121] S1. The nano-alumina powder and the organic solvent are stirred and mixed to obtain a nano-alumina suspension;

[0122] S2. The continuous mesh glass fiber is first impregnated with a nano-alumina suspension, and then the continuous mesh glass fiber after the first impregnation is dried at 80°C for 2h to obtain a pretreated continuous mesh glass fiber;

[0123] S3. Pre-treated continuous mesh glass fiber was secondly impregnated with a coupling agent solution, and then the pre-treated continuous mesh glass fiber after the second impregnation was dried to obtain a modified glass fiber;

[0124] S401. The surface treatment agent and the aluminum nitride thermally conductive powder are stirred and mixed, and then the stirred and mixed mixture is dried to modify the aluminum nitride thermally conductive powder by the surface treatment agent to obtain a surface-modified thermally conductive powder;

[0125] S402. The vinyl silicone oil, gelling agent, adhesive and inhibitor are mixed to obtain a mixing aid;

[0126] S403. The mixing additive and the surface-modified thermally conductive powder are mixed to obtain aluminum nitride thermally conductive silica gel;

[0127] S4. The aluminum nitride thermal conductive silicone and the modified glass fiber are compression molded, and then the molded product is vulcanized and cooled to obtain the aluminum nitride thermal interface material.

[0128] The time for the first infiltration was 15 min, and the time for the second infiltration was 20 min;

[0129] The vulcanization temperature is 130°C and the vulcanization time is 20 minutes.

[0130] Example 2

[0131] Based on the contents disclosed in Example 1, the following modifications are further made:

[0132] The weight m1 of the continuous mesh glass fiber, the weight m2 of the nano alumina powder and the weight m3 of the coupling agent satisfy the relationship: m1:m2:m3=980:10:10.

[0133] The continuous mesh glass fiber includes a plurality of glass fibers, the average diameter of the plurality of glass fibers is 20 μm, and the average distance between two adjacent glass fibers is 200 μm.

[0134] The particle size of nano-alumina powder is 30nm;

[0135] The coupling agent is KH-560.

[0136] In parts by weight, the raw materials of aluminum nitride thermal conductive silicone include:

[0137] Aluminum nitride thermal conductive powder: 2690 parts, vinyl silicone oil: 279 parts, gelling agent: 15 parts, adhesive: 3 parts, inhibitor: 1 part and surface treatment agent: 12 parts.

[0138] In parts by weight, the aluminum nitride thermal conductive powder includes 480 parts of first-grade aluminum nitride powder, 810 parts of second-grade aluminum nitride powder and 1400 parts of third-grade aluminum nitride powder.

[0139] In parts by weight, the surface treatment agent includes: polyvinyl alcohol: 80 parts, KH-570 coupling agent: 10 parts, polybutadiene: 10 parts.

[0140] The vulcanization temperature is 130°C and the vulcanization time is 20 minutes.

[0141] Example 3

[0142] Based on the contents disclosed in Example 1, the following modifications are further made:

[0143] The weight m1 of the continuous mesh glass fiber, the weight m2 of the nano alumina powder and the weight m3 of the coupling agent satisfy the relationship: m1:m2:m3=990:5:5.

[0144] The continuous mesh glass fiber includes a plurality of glass fibers, the average diameter of the plurality of glass fibers is 20 μm, and the average distance between two adjacent glass fibers is 200 μm.

[0145] The particle size of nano-alumina powder is 30nm;

[0146] The coupling agent is KH-560.

[0147] In parts by weight, the raw materials of aluminum nitride thermal conductive silicone include:

[0148] Aluminum nitride thermal conductive powder: 2860 parts, vinyl silicone oil: 139 parts, gelling agent: 7 parts, adhesive: 1.5 parts, inhibitor: 0.5 parts and surface treatment agent: 12 parts.

[0149] In parts by weight, the aluminum nitride thermal conductive powder includes 510 parts of first-grade aluminum nitride powder, 850 parts of second-grade aluminum nitride powder and 1480 parts of third-grade aluminum nitride powder.

[0150] In parts by weight, the surface treatment agent includes: polyvinyl alcohol: 80 parts, KH-570 coupling agent: 10 parts, polybutadiene: 10 parts.

[0151] The vulcanization temperature is 130°C and the vulcanization time is 20 minutes.

[0152] Example 4

[0153] Based on the contents disclosed in Example 1, the following modifications are further made:

[0154] The weight m1 of the continuous mesh glass fiber, the weight m2 of the nano alumina powder and the weight m3 of the coupling agent satisfy the relationship: m1:m2:m3=990:5:5.

[0155] The continuous mesh glass fiber includes a plurality of glass fibers, the average diameter of the plurality of glass fibers is 30 μm, and the average distance between two adjacent glass fibers is 280 μm.

[0156] The particle size of nano-alumina powder is 60nm;

[0157] The coupling agent is a mixture of KH-560 and KH-570.

[0158] In parts by weight, the raw materials of aluminum nitride thermal conductive silicone include:

[0159] Aluminum nitride thermal conductive powder: 2820 parts, vinyl silicone oil: 140 parts, gelling agent: 8 parts, adhesive: 1.5 parts, inhibitor: 0.5 parts and surface treatment agent: 30 parts.

[0160] In parts by weight, the aluminum nitride thermal conductive powder includes 505 parts of first-grade aluminum nitride powder, 845 parts of second-grade aluminum nitride powder and 1470 parts of third-grade aluminum nitride powder.

[0161] In parts by weight, the surface treatment agent includes: polyvinyl alcohol: 90 parts, KH-570 coupling agent: 5 parts, polybutadiene: 5 parts.

[0162] The vulcanization temperature is 120°C and the vulcanization time is 30 minutes.

[0163] Example 5

[0164] Based on the contents disclosed in Example 1, the following modifications are further made:

[0165] The weight m1 of the continuous mesh glass fiber, the weight m2 of the nano alumina powder and the weight m3 of the coupling agent satisfy the relationship: m1:m2:m3=990:5:5.

[0166] The continuous mesh glass fiber includes a plurality of glass fibers, the average diameter of the plurality of glass fibers is 30 μm, and the average distance between two adjacent glass fibers is 280 μm.

[0167] The particle size of nano-alumina powder is 60nm;

[0168] The coupling agent is a mixture of KH-560 and KH-570.

[0169] In parts by weight, the raw materials of aluminum nitride thermal conductive silicone include:

[0170] Aluminum nitride thermal conductive powder: 2878.5 parts, vinyl silicone oil: 100 parts, gelling agent: 5 parts, adhesive: 1.0 parts, inhibitor: 0.5 parts and surface treatment agent: 15 parts.

[0171] In parts by weight, the aluminum nitride thermal conductive powder includes 530 parts of first-grade aluminum nitride powder, 860 parts of second-grade aluminum nitride powder and 1488.5 parts of third-grade aluminum nitride powder.

[0172] In parts by weight, the surface treatment agent includes: polyvinyl alcohol: 90 parts, KH-570 coupling agent: 5 parts, polybutadiene: 5 parts.

[0173] The vulcanization temperature is 120°C and the vulcanization time is 30 minutes.

[0174] Comparative Example 1

[0175] Based on the contents disclosed in Example 1, the following modifications are further made:

[0176] No continuous mesh glass fibers are added.

[0177] Comparative Example 2

[0178] Based on the contents disclosed in Example 1, the following modifications are further made:

[0179] No nano alumina powder is added.

[0180] Comparative Example 3

[0181] Based on the contents disclosed in Example 1, the following modifications are further made:

[0182] The weight m1 of the continuous mesh glass fiber, the weight m2 of the nano alumina powder and the weight m3 of the coupling agent satisfy the relationship: m1:m2:m3=935:60:5.

[0183] Comparative Example 4

[0184] Based on the contents disclosed in Example 1, the following modifications are further made:

[0185] The first infiltration time was 10 min, and the second infiltration time was 15 min;

[0186] Related experiments and effect data:

[0187] The performance tests of the aluminum nitride thermal interface materials obtained in each embodiment and comparative example were respectively carried out, wherein the thermal conductivity of the aluminum nitride thermal interface material was measured according to the ASTM D5470 standard and the DRL-Ⅲ series thermal conductivity test, and then the hardness of the aluminum nitride thermal interface material was tested by a Shore hardness tester according to the ASTM D22405 standard, and then the density of the aluminum nitride thermal interface material was measured by the water displacement method, and then the compression rate of the aluminum nitride thermal interface material was tested according to the ASTM D2240 standard, and then the volume resistivity of the aluminum nitride thermal interface material was tested according to the ASTM D257 standard. The test results are shown in Table 1.

[0188] Table 1 Performance test results of aluminum nitride thermal interface materials obtained in various embodiments and comparative examples

[0189]

[0190] As can be seen from Table 1, an aluminum nitride thermal interface material with high compressive strength provided in an embodiment of the present application comprises a continuous mesh glass fiber that is surface modified by nano-alumina powder and a coupling agent, and then the continuous mesh glass fiber is used as a support body. The compressive strength of the aluminum nitride thermal interface material can be increased to more than 100 MPa based on the strength and toughness characteristics of the continuous mesh glass fiber; in addition, the thickness of the aluminum nitride thermal interface material can be controlled within the range of 0.3 mm to 2.0 mm, and the Shore hardness of the aluminum nitride thermal interface material is 30 to 70; in addition, under the condition of 10 ps, ​​the compression rate of the aluminum nitride thermal interface material is ≥30%, and these aluminum nitride thermal interface materials can be used in spacecraft and more sophisticated thermally conductive and insulating electronic products.

[0191] In addition, the present application provides an aluminum nitride thermal interface material with high compressive strength, wherein aluminum nitride powders with multiple particle sizes and surface treatments are compounded in aluminum nitride thermal conductive silica gel as aluminum nitride thermal conductive powders, and the thermal conductivity of the aluminum nitride thermal interface material can reach a range of 8W / (m·K) to 13W / (m·K), and the volume resistivity of the aluminum nitride thermal interface material is ≥10 13 Ω·m, the density of the aluminum nitride thermal interface material is ≤3.5g / cm 3 .

[0192] The above is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. It will be apparent to those skilled in the art that various modifications to these embodiments are possible, and the general principles defined in the present application can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to these embodiments shown in the present application, but will conform to the widest scope consistent with the principles and novel features applied for by the present application.

Claims

1. An aluminum nitride thermal interface material with high compressive strength, characterized in that: The aluminum nitride thermal interface material comprises: Modified glass fiber; and at least one layer of aluminum nitride thermally conductive silicone, wherein at least one layer of the aluminum nitride thermally conductive silicone is disposed on one side surface or both sides surface of the modified glass fiber; The raw materials of the modified glass fiber include: continuous mesh glass fiber, nano alumina powder and a coupling agent. The weight m1 of the continuous mesh glass fiber, the weight m2 of the nano alumina powder and the weight m3 of the coupling agent satisfy the relationship: m1:m2:m3=(950-1000):(5-50):(0-30).

2. The aluminum nitride thermal interface material according to claim 1, characterized in that: The continuous mesh glass fibers include a plurality of glass fibers, the average diameter of the plurality of glass fibers is 2 μm to 30 μm, and the average distance between two adjacent glass fibers is 20 μm to 300 μm.

3. The aluminum nitride thermal interface material according to claim 1, characterized in that: The particle size of the nano alumina powder is 15nm to 100nm; The coupling agent includes at least one of the following: KH-550 coupling agent, KH-560 coupling agent and KH-570 coupling agent.

4. The aluminum nitride thermal interface material according to claim 1, characterized in that: In parts by weight, the raw materials of the aluminum nitride thermal conductive silica gel include: Aluminum nitride thermal conductive powder: 2600 parts to 2880 parts, vinyl silicone oil: 100 parts to 300 parts, gelling agent: 5 parts to 15 parts, adhesive: 1 part to 3 parts, inhibitor: 0.01 parts to 1 part and surface treatment agent: 10 parts to 90 parts.

5. The aluminum nitride thermal interface material according to claim 4, characterized in that: In parts by weight, the aluminum nitride thermal conductive powder comprises 480 to 520 parts of first-grade aluminum nitride powder, 800 to 870 parts of second-grade aluminum nitride powder, and 1400 to 1500 parts of third-grade aluminum nitride powder; The particle size of the first-grade aluminum nitride powder is 0.6 μm to 1.0 μm, the particle size of the second-grade aluminum nitride powder is 8 μm to 12 μm, and the particle size of the third-grade aluminum nitride powder is 118 μm to 122 μm.

6. The aluminum nitride thermal interface material according to claim 4, characterized in that: In parts by weight, the surface treatment agent includes: polyvinyl alcohol: 30 parts to 100 parts, KH-570 coupling agent: 1 part to 10 parts, polybutadiene: 5 parts to 20 parts.

7. The aluminum nitride thermal interface material according to claim 4, characterized in that: The viscosity of the vinyl silicone oil is 20 cPs to 200 cPs; The gelling agent includes hydrogen-containing silicone oil; The adhesive includes a platinum catalyst.

8. A method for preparing the aluminum nitride thermal interface material according to any one of claims 1 to 7, characterized in that: The method comprises: The nano-alumina powder and the organic solvent are stirred and mixed to obtain a nano-alumina suspension; Using the nano-alumina suspension to first impregnate the continuous mesh glass fiber, and then drying the first impregnated continuous mesh glass fiber to obtain pretreated continuous mesh glass fiber; Using a coupling agent solution to perform a second impregnation on the pretreated continuous mesh glass fiber, and then drying the pretreated continuous mesh glass fiber after the second impregnation to obtain a modified glass fiber; The aluminum nitride thermal conductive silica gel and the modified glass fiber are compression molded, and then the molded product is vulcanized and cooled to obtain the aluminum nitride thermal interface material.

9. The method according to claim 8, characterized in that The first infiltration time is ≥15 min, and the second infiltration time is ≥20 min; The vulcanization temperature is 100° C. to 130° C., and the vulcanization time is 15 min to 35 min.

10. The method according to claim 8, characterized in that The method further comprises: The surface treatment agent and the aluminum nitride thermal conductive powder are stirred and mixed, and then the stirred and mixed mixture is dried to modify the aluminum nitride thermal conductive powder by the surface treatment agent to obtain a surface-modified thermal conductive powder; Mixing vinyl silicone oil, a gelling agent, an adhesive and an inhibitor to obtain a mixing auxiliary agent; The mixing aid and the surface-modified thermally conductive powder are mixed to obtain aluminum nitride thermally conductive silica gel.